Condom
By developing reversible hydrogen bond cross-linked hydrogel copolymers, the problem of existing condom materials taking into account the softness and mechanical strength is solved, and a softer, more lubricating and less likely to break condoms are achieved, improving the use of Experience and security.
Patent Information
- Application Number
- CN202380044326.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-04-14
- Filing Date
- 2023-04-14
- Publication Date
- 2025-01-10
AI Technical Summary
Existing condom materials are difficult to balance between softness, lubricity and mechanical strength, resulting in poor usage experience and easy to breakage, and most materials have unpleasant odors and risk of allergic reactions.
A hydrogel copolymer based on reversible hydrogen bond crosslinking was developed to form a copolymer with high water content and good lubricating properties through the reaction of monomer A with monomer B, C and D, combining optimized molar ratios and monomers Body selection, and condoms with high softness and mechanical strength were prepared.
It achieves a softer, lubricant and less likely to break the condom without damaging mechanical strength, reducing the risk of discomfort and allergic reactions, while improving the transparency and usage experience of the condom.
Smart Images

Figure CN119300792A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of condoms, and in particular relates to hydrogel condoms, their packaging forms, and methods for manufacturing the same. Background Art
[0002] Today's consumers have a wide selection of contraceptives available for pregnancy prevention. However, condoms are the only contraceptives that offer protection against sexually transmitted infections (STIs) such as chlamydia and HIV. Condoms form a physical barrier to the transfer of bodily fluids, viruses, and other microorganisms between sexual partners. Therefore, the material chosen to manufacture condoms is crucial; it must have low permeability to these fluids and microorganisms while also being strong enough to resist bursting, breaking, or tearing during sexual activity.
[0003] On the other hand, condom materials should ideally be flexible and able to stretch to accommodate users of different sizes. Furthermore, the softness of the material is a very important parameter. A significant proportion of people who choose not to use condoms do so because they don't like the feel of them. From a public health perspective, as well as in the interests of individual consumers, developing a material that feels softer, more natural, and more skin-like, while still being tough enough for condom use, would be highly beneficial.
[0004] Most condoms currently on the market are made from natural rubber latex ("NRL"), synthetic polyisoprene ("PI"), or polyurethane ("PU"). Although all of these materials are capable of performing the basic barrier function of a condom, each has its own disadvantages. NRL has an unpleasant odor and taste that need to be masked, and causes latex allergies in some people. Of the so-called "latex-free" materials, PU is harder and less stretchable than NRL and PI, and generally feels more uncomfortable. PI still has some of the unpleasant odor and taste of NRL and cannot currently be made as thin as PU. In addition, all three materials have an inherent degree of stickiness and friction that makes them feel rough to the touch, and commercial condoms made from these materials typically have a separate lubricant pre-applied to their surface.
[0005] Many alternative materials have been studied in the art. For example, carboxylated nitrile rubber has been suggested for use in condoms, see, for example, US5,195,537 (Tillotson Corporation). Other materials described in the literature include polyvinylidene chloride or low-density polyethylene mixed with polyisobutylene and / or polyethylene-vinyl acetate copolymer, see US 2015 / 0313752 (Abadi); and styrene-polyisoprene-styrene latex, see WO 2021 / 124215 (Church & Dwight).
[0006] WO2020 / 257880 (Eudaemon Technologies) describes condoms made of polyether or polyester polyurethane hydrogels. The molecular weight of the polyurethane is about 40,000-500,000 Da, preferably derived from the polymerization of 4,4'-dicyclohexylmethane diisocyanate with ether or ethyl ester. WO2021 / 130625 (Church & Dwight) aims to improve the inherent lubricity of latex condoms by coating them with a hydrogel / latex blend layer. The blend layer is, for example, polyethylene oxide blended with natural rubber latex.
[0007] None of these materials have challenged established commercial NRL, PI, or PU materials on the market. Many materials that are pleasant to the touch are inherently fragile and unsuitable for the condom market, where minimizing breakage is paramount. Therefore, providing condoms that meet these conflicting technical requirements is a challenge. Summary of the Invention
[0008] In a first aspect of the present invention, a condom according to claim 1 is provided.
[0009] In a second aspect of the present invention, a package is provided, which encapsulates the condom of the first aspect of the present invention.
[0010] In a third aspect of the present invention, a method for manufacturing a condom as claimed in claim 14 is provided.
[0011] In a fourth aspect of the present invention there is provided the use of a film comprising the copolymer used in the first aspect of the present invention in the form of a hydrogel as a physical barrier during sexual activity. DETAILED DESCRIPTION
[0012] Embodiments described herein with respect to one aspect of the invention may be combined with each other and are equally applicable to other aspects of the invention, unless specified to the contrary or the context requires otherwise.
[0013] The present inventors have developed condoms made from the copolymers described herein, which are based on the copolymers outlined in WO2006 / 118460, EP1972661A1, and WO2014 / 185779. These documents are particularly concerned with providing hydrogels that can be reversibly switched between liquid and gel states (e.g., by changing temperature, polymer concentration, or solvent polarity / ionic strength). The materials are disclosed for various applications, including biomedical applications such as scaffolds for tissue engineering and biodegradable implants; however, there is no disclosure of condoms or use during sexual activity.
[0014] Hydrogels are typically highly cross-linked polymers that are able to swell to absorb high water contents (up to 95% by weight) within the polymer network. The water in the hydrogel provides advantageous lubricating properties. However, there is a trade-off between the lubricity and mechanical strength of the material. In traditional types of hydrogels, higher levels of cross-linking result in greater material strength but lower water-holding capacity and, therefore, lower lubricity; lower levels of cross-linking produce a smoother but more fragile material.
[0015] In the present invention, the copolymer is reversibly cross-linked via hydrogen bonding. Monomer A reacts with monomer B to form a substance comprising ureidopyrimidone or UPy units. As shown below, two UPy units can form a quadruple hydrogen bond pair that acts as a strong reversible cross-linker.
[0016]
[0017] In one embodiment, monomer A has the formula:
[0018]
[0019] where R 1 and R 2 independently selected from H and C1-C1 optionally substituted with a single hydroxyl, primary or secondary amine group 20 Preferably, the hydroxyl group or the amine group is located at the terminal carbon atom. In one embodiment, R 1 and R 2 One of the Rs carries a single hydroxyl group, preferably on a terminal carbon. 1 and R 2 The other of is unsubstituted. In one embodiment, R 2 In one embodiment, R 1 and R 2 independently selected from H and C1, C2, C3, C4, C5, C6, C7, C8, C9 and C1, each optionally substituted with a single hydroxyl, primary or secondary amine group 10 In one embodiment, R 1 and R 2 One of the following, preferably R 1 , is H or C1-C3 alkyl, preferably methyl or ethyl, preferably methyl. In one embodiment, R 1 and R 2 one of (preferably the other one defined in the above embodiment), preferably R 2 , is a C1-C5 alkyl group (preferably a C2-C4 alkyl group, preferably a C2 or C3 alkyl group, preferably a C2 alkyl group) substituted with a hydroxyl group, preferably on a terminal carbon atom, preferably -CH2CH2OH. In one embodiment, R 1 is H or C1-C3 alkyl, and R2 is a C1-C5 alkyl group substituted by a (preferably terminal) hydroxyl group or a primary amino group, preferably a hydroxyl group.
[0020] Preferably, monomer A has the formula:
[0021]
[0022] Monomer B is of formula OCN-R 3 -NCO diisocyanate, where R 3 It is C4-C 20 R3 can be linear or optionally cyclic or branched. In one embodiment, monomer B is of the formula OCN-R 3 -NCO diisocyanate, where R 3 is an alkylene group having: at least 5 C atoms, at least 6 C atoms, at least 7 C atoms, at least 8 C atoms, at least 9 C atoms, at least 10 C atoms, at least 11 C atoms, at least 12 C atoms, or at least 13 C atoms; and / or at most 19 C atoms, at most 18 C atoms, at most 17 C atoms, at most 16 C atoms, at most 15 C atoms, at most 14 C atoms, or at most 13 C atoms. In one embodiment, R 3 C5-C 18 Alkylene, preferably C6-C 15 In one embodiment, R 3 C9-C 14 Alkylene or C 10 -C 13 Alkylene. For example, R 3 It can be C6 alkylene, C9 alkylene, C 10 Alkylene or C 13 In one embodiment, R 3 In one embodiment, monomer B is hexamethylene diisocyanate (HDI).
[0023] In one embodiment, R 3 Including cyclic alkylene, preferably cyclohexylene. In one embodiment, R 3 Contains 1 or 2 cyclohexylene groups. Preferably, R 3 Preferably, monomer B is methylene-dicyclohexyl-4,4'-diisocyanate (HMDI). Alternatively, when R 3 When containing 1 cyclohexylene group, preferably, R 3 C9 or C 10 Preferably, monomer B is isophorone diisocyanate (IPDI).
[0024] Monomer C is a hydroxyl-terminated telechelic polyalkylene glycol having a number average molecular weight of 1000 to 10,000 Da. In one embodiment, the hydroxyl-terminated telechelic polyalkylene glycol monomer C is linear. In one embodiment, it is polyethylene glycol, polypropylene glycol or polyethylene-polypropylene glycol (which can be, for example, a random copolymer, an alternating copolymer or a block copolymer). In one embodiment, the number average molecular weight determined by its hydroxyl number is: at least 1500 Da, at least 2000 Da, at least 2500 Da, at least 3000 Da, at least 3500 Da or at least 4000 Da; and / or no more than 8000 Da, no more than 7000 Da, no more than 6000 Da, no more than 5000 Da, or no more than 4500 Da. For example, its number average molecular weight can be 2000-7000 Da or 2500-4500 Da. In one embodiment, the number average molecular weight of monomer C can be 2500-3500 Da, preferably 2800-3200 Da, preferably 3000 Da or about 3000 Da. In one embodiment, the number average molecular weight can be 3500-4500 Da, preferably 3800-4200 Da, preferably 4000 Da or about 4000 Da. In one embodiment, the number average molecular weight of monomer C can be 3000-4000 Da, preferably 3200-3800 Da, preferably 3400-3600 Da, preferably 3500 Da or about 3500 Da.
[0025] Monomer D is of the formula HO-R 4 -OH diol, where R 4 is a C2-C4-C6 ... 20 Alkylene. R 4 Can be linear or optionally branched, cyclic or contain cyclic groups. In one embodiment, R 4 In one embodiment, R 4 is an alkylene group having: at least 4 C atoms, at least 5 C atoms, at least 6 C atoms, at least 7 C atoms, at least 8 C atoms, at least 9 C atoms, at least 10 C atoms, at least 11 C atoms, or at least 12 C atoms; and / or up to 18 C atoms, up to 17 C atoms, up to 16 C atoms, up to 15 C atoms, up to 14 C atoms, up to 13 C atoms, up to 12 C atoms, up to 11 C atoms, up to 10 C atoms, up to 9 C atoms, or up to 8 C atoms; in each case, optionally interrupted by 1 to 5 heteroatoms (preferably 1 or 2 heteroatoms) selected from the group consisting of O, N and S, preferably O. For example, R 4It may be an alkylene group having 4 to 16 C atoms, 5 to 15 C atoms, 6 to 12 C atoms, 6 to 8 C atoms or 10 to 14 C atoms. 4 is not interrupted by any heteroatoms. Monomer D may be, for example, 1,6-hexanediol, 1,10-decanediol or 1,12-dodecanediol. In one embodiment, R 4 including cyclic alkylene, preferably cyclohexylene, preferably, wherein R 4 is not interrupted by any heteroatoms. 4 Preferably, monomer D is 1,4-cyclohexanedimethanol (preferably a cis-trans racemic mixture). Without wishing to be bound by theory, it is believed that the cyclohexylene group may increase the toughness of the resulting polymer.
[0026] In another embodiment, R 4 is interrupted by 1 or 2 O atoms, preferably 1 O atom. For example. R 4 It may be an alkylene radical having 2 to 8 C atoms, 3 to 7 C atoms or 4 to 6 C atoms, which is in each case interrupted by 1 or 2 O atoms. Thus, monomer D may be, for example, diethylene glycol or triethylene glycol.
[0027] In one embodiment, monomer D is solid at 25° C. Preferably, the melting point of monomer D is: ≥30° C., ≥40° C., ≥50° C., ≥60° C., ≥70° C., ≥75° C., or ≥80° C.; and / or ≤120° C., ≤110° C., ≤100° C., ≤90° C., or ≤85° C. For example, the melting point of monomer D may be 40-100° C., 50-90° C., or 70-85° C., or 75-83° C.
[0028] Without wishing to be bound by theory, the relatively long chain R in monomer D 4 The groups and / or relatively high melting point can contribute to the formation of copolymers having excellent stability to thermal degradation during storage. The resulting materials can also result in condoms that are particularly comfortable to the touch and / or less sticky when worn.
[0029] In one embodiment, the molar ratio of monomers D to C is at least 0.5:1, at least 1:1, at least 1.5:1, at least 2:1, at least 3:1, at least 4:1, or at least 5:1; and / or no more than 9:1, no more than 8:1, no more than 7:1, no more than 6:1, no more than 5:1, no more than 4.7:1, or no more than 4.5: 1. In one embodiment, the molar ratio of monomers D to C is from 3:1 to 6:1, from 3.2:1 to 5:1, or from 3.5:1 to 4.7:1.
[0030] The optimal ratio of monomers D to C may depend on the number average molecular weight of monomer C and / or the choice of monomer D. In one embodiment, the number average molecular weight of monomer C is 2500 to 3500 Da, and the molar ratio of monomers D to C is 1.5-6.5; preferably, the number average molecular weight of monomer C is 3000 Da, and the molar ratio of monomers D to C is 2-6, 3-5, or 4. In one embodiment, the number average molecular weight of monomer C is 3500 to 4500 Da, and the molar ratio of monomers D to C is 4.5-8.5, 5-8, or 5.5-7; preferably, the number average molecular weight of monomer C is 4000 Da, and the molar ratio of monomers D to C is 4-8, 5-7, or 6. Preferably, in the embodiments of this paragraph, monomer D is 1,6-hexanediol.
[0031] In one embodiment:
[0032] a) Monomer C has a number average molecular weight of 2500 to 5000 Da, 2700 to 4500 Da, 2800 to 4200 Da, 3000 to 4000 Da, 3000 Da, or about 3000 Da;
[0033] b) the molar ratio of monomers D to C is: at least 3, at least 3.2, at least 3.5, at least 4, at least 4.5, or at least 4.7; and / or at most 6, at most 5.5, at most 5.0, or at most 4.8; preferably 3-6, 3.2-5, 3.5-4.8, 4-4.7, 4.5, or about 4.5; and
[0034] c) Monomer D: Formula HO-R 4 -OH diol, where R 4 is an alkylene group having 10-14 C atoms, preferably 11-13 C atoms, preferably 12 C atoms, preferably, wherein monomer D is 1,12-dodecanediol; or has a melting point of ≥70°C, preferably 75-85°C.
[0035] In one embodiment, the molar ratio of monomer B to the sum of monomers A+C+D is: at least 0.9, at least 0.95, or at least 0.98; and / or at most 1.1, at most 1.05, or at most 1.02. Preferably, the molar ratio of monomer B to the sum of monomers A+C+D is 0.9-1.1, 0.95-1.05, 0.98-1.02, about 1 or 1.00.
[0036] In one embodiment, copolymer X has a weight average molecular weight of 5 to 140 kDa, preferably: ≥10 kDa, ≥20 kDa, ≥30 kDa, ≥40 kDa, ≥50 kDa, ≥60 kDa, or ≥70 kDa; and / or ≤130 kDa, ≤120 kDa, ≤110 kDa, ≤100 kDa, ≤95 kDa, ≤90 kDa, ≤85 kDa, or ≤80 kDa; preferably 50-80 kDa; as determined by size exclusion chromatography at 50°C in DMF containing 10 mM LiBr using PEO / PEG standards. However, the weight average molecular weight of copolymer X will be affected by the molecular weight of the monomers used to form it. Preferably, the weight average molecular weight described in this paragraph applies to embodiments in which monomer D is 1,6-hexanediol.
[0037] In one embodiment:
[0038] a) Monomer D: Formula HO-R 4 -OH diol, where R 4 is an alkylene group having 10-14 C atoms, preferably 11-13 C atoms, preferably 12 C atoms, preferably, wherein monomer D is 1,12-dodecanediol; or has a melting point of ≥70°C, preferably 75-85°C; and
[0039] b) the weight average molecular weight of copolymer X is: ≥70 kDa, ≥75 kDa, ≥80 kDa, ≥85 kDa, ≥90 kDa, ≥95 kDa, ≥100 kDa, or ≥105 kDa; and / or ≤130 kDa, ≤120 kDa or ≤110 kDa; preferably 80-120 kDa, 85-115 kDa, or 90-110 kDa.
[0040] In an embodiment, copolymer X is a random copolymer.
[0041] In one embodiment, copolymer X can be obtained by reacting monomers A (or tautomers thereof), B, and C together in the same reaction mixture to form a reaction product, preferably followed by polymerizing the reaction product with monomer D.
[0042] In another embodiment, copolymer X can be obtained by reacting monomers A (or tautomers thereof), B, C, and D together in the same reaction mixture to form a reaction product.
[0043] The reaction can optionally be catalyzed, for example using catalysts known in the art for the reaction of isocyanates with hydroxyl groups. Examples of suitable catalysts are given in WO2006 / 118460 and WO2014 / 185779, and include tin compounds such as dibutyltin dilaurate. Alternatively, the reaction can be carried out in the absence of a tin catalyst or in the absence of a catalyst at all.
[0044] In a particularly preferred embodiment, 2-amino-4-hydroxy-5-(2-hydroxyethyl)-6-methyl-pyrimidine (or its tautomer) is reacted with polyethylene glycol, a diisocyanate, and a diol (HO-R-OH). The diisocyanate is preferably HMDI, methylene dicyclohexyl-4,4'-diisocyanate. The diol is preferably 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,4-cyclohexanedimethanol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, or 1,12-dodecanediol, preferably 1,6-hexanediol, 1,4-cyclohexanedimethanol, or 1,12-dodecanediol. The polyethylene glycol is preferably PEG1000-PEG6000, preferably PEG3000-PEG4000.
[0045] In one embodiment, monomer A is 2-amino-4-hydroxy-5-(2-hydroxyethyl)-6-methyl-pyrimidine, monomer B is methylene dicyclohexyl-4,4'-diisocyanate, monomer C is a linear polyethylene glycol having a number average molecular weight of 2000-6000, monomer D is 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,4-cyclohexanedimethanol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol or 1,12-dodecanediol, and the molar ratio of monomer D to C is 3:1 to 8:1.
[0046] In one embodiment, monomer A is 2-amino-4-hydroxy-5-(2-hydroxyethyl)-6-methyl-pyrimidine, monomer B is methylene dicyclohexyl-4,4'-diisocyanate, monomer C is PEG2800-4500 (preferably PEG3000-4200, preferably PEG4000), monomer D is 1,6-hexanediol, and the molar ratio of monomer D to C is 3-7 (preferably 4-6.5 or 5-6). In one embodiment, monomer A is 2-amino-4-hydroxy-5-(2-hydroxyethyl)-6-methyl-pyrimidine, monomer B is methylene dicyclohexyl-4,4'-diisocyanate, monomer C is PEG2800-3500 (preferably PEG2900-3200, preferably PEG3000), monomer D is 1,12-dodecanediol, and the molar ratio of monomer D to C is 2-6 (preferably 3-5, 3.5-4.7 or 4-4.5).
[0047] In each of the above cases, the present invention can use mixtures of different monomers A and / or mixtures of different monomers B and / or mixtures of different monomers C and / or mixtures of different monomers D. However, preferably, only a single monomer A and / or B and / or C and / or D is used (preferably a single monomer from each of monomers A, B, C and D). When mixtures of different monomers A, B, C and / or D are used, the amounts mentioned above relate to the total amount of the corresponding monomer types, for example the molar ratio D:C means the molar ratio of all monomers D: the molar ratio of all monomers C.
[0048] In one embodiment, the condom contains more than one type of copolymer X. For example, different layers of the condom may contain different copolymers X. In one embodiment, the different copolymer X materials are present together as a blend. For example, the blend may contain a first copolymer X and a second copolymer X in a weight ratio of at least 1:1, at least 1.5:1, at least 2:1, at least 3:1, at least 4:1, at least 5:1, at least 6:1, at least 7:1, at least 8:1, or at least 9:1; and / or at most 50:1, at most 40:1, at most 30:1, at most 20:1, at most 15:1, at most 10:1, or at most 9:1. In one embodiment, the blend contains the first copolymer X and the second copolymer X in a weight ratio of 1:1 to 50:1, 1.5:1 to 20:1, or 2:1 to 9:1. In one embodiment, the first copolymer X has a higher tensile strength but a higher E100 than the second copolymer X. Thus, mixing a softer material with a stronger material can achieve a good balance of properties.
[0049] In one embodiment, the condom is hydrated with water, and the one or more copolymers X are in the form of a hydrogel. Preferably, the condom comprises: ≥20 wt% water, ≥30 wt% water, ≥40 wt% water, ≥50 wt% water, ≥60 wt% water, ≥65 wt% water, or ≥70 wt% water; and / or ≤95 wt% water, ≤90 wt% water, ≤85 wt% water, ≤80 wt% water, or ≤75 wt% water, based on the total weight of the condom. For example, it may comprise 60-95 wt% water, 65-85 wt% water, or 70-80 wt% water. If the water content is too high, the condom may be too fragile, but a water content higher than the water content of the skin is desirable for a soft and lubricated feel. In one embodiment, the condom has an equilibrium water content of the values recited in this paragraph after swelling in water at 25°C for 24 hours. It will be appreciated that the actual water content of the condom may vary over time, depending on the environmental conditions in which it is stored.
[0050] Condoms can take the general shape of a tubular body with an open end and a closed end. They can be "male" condoms (intended to be worn on the penis) or "internal" condoms (intended to be inserted into the vagina or anus before sexual activity). Preferably, they are male condoms. Condoms can be entirely straight-walled or have a shape with variable width along their length, for example. They can have a protrusion or reservoir at the closed end to hold semen.
[0051] In an embodiment of the invention, the condom is at least 120 mm long, or at least 130 mm long, at least 140 mm long, at least 150 mm long, at least 160 mm long, at least 170 mm long, or at least 180 mm long; and / or no more than 230 mm long, or no more than 220 mm long, or no more than 210 mm long, or no more than 200 mm long. In one embodiment, the condom is 120-230 mm long, or 160-200 mm long. These lengths are measured as the longest dimension from the open end to the closed end of the condom.
[0052] Optionally, the maximum width of the condom (measured when lying flat) can be: at least 40mm, at least 45mm, at least 50mm, at least 51mm, at least 52mm, at least 53mm, at least 54mm, at least 55mm, at least 56mm, at least 57mm, at least 58mm, at least 59mm or at least 60mm; and / or no more than 80mm, no more than 75mm, no more than 70mm, no more than 65mm, no more than 64mm, no more than 63mm, no more than 62mm, no more than 61mm or no more than 60mm. In one embodiment, the maximum width of the condom is 40-80mm or 45-70mm. "Maximum width" refers to the width of the condom at its widest point (taking into account that the width can vary in the case of shaped condoms).
[0053] In the past, consumers have demanded thinner and thinner condoms because it is believed that this makes the sensation during sexual activity more natural. Thinner condoms made from traditional materials are also more likely to be more transparent. However, the condoms of the present invention can provide an inherently pleasant tactile sensation and have high transparency, making their thickness less detrimental. In one embodiment, the condom has a thickness of at least 20 microns, at least 30 microns, at least 40 microns, at least 50 microns, at least 60 microns, at least 70 microns, at least 80 microns, at least 90 microns, or at least 100 microns; and / or at most 300 microns, at most 250 microns, at most 200 microns, at most 150 microns, or at most 120 microns. For example, its thickness can be 20-300 microns, 70-200 microns, 80-150 microns, or 90-120 microns.
[0054] In an embodiment of the invention, the pore size of the condom is less than 30 nm, less than 29 nm, less than 28 nm, less than 27 nm, less than 26 nm or less than 25 nm.
[0055] During the process of rolling up the condom, the material can stretch. Because condoms can stretch while being worn, and the rolling process can also stretch the material slightly, the dimensions described herein are measured in the relaxed, unrolled state of the condom. Furthermore, because the hydrogel material swells with water absorption, the dimensions described herein are measured on a condom with its equilibrium water content at 25°C and without a load.
[0056] The condom may consist solely of one or more copolymers X and water. In one embodiment, the condom may be transparent and / or colorless. Since no chemical crosslinking agents, curing agents, or other additives are required to form the condom from the aqueous formulation of the copolymer, the condom of the present invention may be made with high transparency compared to natural rubber latex condoms. Preferably, the absorbance at 350 nm is ≤1 mm per mm of condom thickness. -1 , ≤0.9mm -1 , ≤0.8mm -1 , ≤0.7mm -1 , ≤0.6mm -1 , ≤0.4mm -1 , ≤0.3mm -1 , ≤0.2mm -1 , ≤0.1mm -1 or ≤0.05mm -1 , and / or the absorbance at 400nm per mm thickness of the condom is ≤1mm -1 , ≤0.9mm -1 , ≤0.8mm -1 , ≤0.7mm -1 , ≤0.6mm -1 , ≤0.4mm -1 , ≤0.3mm -1 , ≤0.1mm -1 , ≤0.05mm -1 or ≤0.02mm -1 This was measured using UV / vis spectroscopy on 1 cm x 1 cm films cut from the condom in its unfolded state.
[0057] On the other hand, desired additives can be included in the condom to enhance its appeal to consumers. For example, the condom can be colored, for example by hydrating the condom in an aqueous formulation containing one or more colorants, preferably hydrophilic colorants. Similarly, the condom can contain any one or more spices, fragrances, sensates (e.g., agents that provide a warming, cooling, or tingling sensation), antimicrobials, spermicides, or pH regulators. It can contain agents, such as agents that prevent premature ejaculation, such as benzocaine, or agents that provide orgasm enhancement. Alternatively, or in addition to being incorporated into the condom hydration liquid, one or more of these additives can be present in the liquid that forms the initial film, such as the liquid in which the condom mold is immersed. Another option is to include additives in the reaction mixture used to synthesize copolymer X, provided that these additives do not interfere with the copolymerization reaction.
[0058] If it is desired that the additive remain in a localized area of the condom and not be distributed throughout the entire condom, this can be achieved by applying a suitable formulation after the condom has been formed and hydrated. For example, a high viscosity benzocaine formulation can be dosed into the tip of the condom after manufacture.
[0059] In its hydrated state, the condom can have high inherent lubricity. However, if additional lubricity is desired, the condom can contain other lubricants besides water, such as water-absorbing polysaccharides. The lubricant can be synthetic or derived from natural resources. Examples of suitable lubricants include carrageenan, alginates, agar, agarose, pectin, dextran, xanthan gum, gum arabic, hyaluronic acid, chondroitin sulfate, starch, chitosan, cyclodextrin, guar gum, cellulose, polyacrylic acid, or polyacrylamide. Preferably, the lubricant does not gel at the concentration used. If the lubricant is carrageenan, lamba-carrageenan is preferred over iota-carrageenan, and iota-carrageenan is preferred over kappa-carrageenan. The lubricant can be introduced into the condom by hydrating it in water containing the lubricant in a dissolved or dispersed state, preferably a dissolved state. Compared to traditional lubricants that are applied only to the surface of latex condoms, when a lubricant is introduced into a hydrogel in this manner, the lubricant is incorporated into the body of the condom as well as on the surface, and is therefore less likely to fall off during sexual activity. Alternatively, a lubricant (preferably a hydrophilic lubricant, such as a traditional water-based lubricant) or other fluid material can be applied to the surface of the condom after hydration. Alternatively, the lubricant can be dissolved or dispersed in the liquid that forms the initial film, such as an impregnation solution. Another option may be to include a lubricant in the reaction mixture used to synthesize copolymer X.
[0060] The lubricant can be incorporated into the condom in any suitable amount. In one embodiment, the condom comprises a lubricant in an amount of ≤5 wt%, preferably ≤4 wt%, ≤3 wt%, ≤2 wt%, ≤1 wt%, or ≤0.5 wt%; and / or ≥0.01 wt%, ≥0.02 wt%, ≥0.05 wt%, ≥0.1 wt%, ≥0.2 wt%, or ≥0.25 wt%. The desired concentration may vary depending on the pH of the solution to minimize gelation.
[0061] In its hydrated state, the condom can be easily rolled and unrolled without the need for any finishing powder. Preferably, no finishing powder is used on the condom.
[0062] In one embodiment, the condom has a Young's modulus of ≤5 MPa, ≤4 MPa, ≤3.5 MPa, ≤3 MPa, ≤2.5 MPa or ≤2.0 MPa at 100% strain (E100). In one embodiment, the condom has a toughness of ≥5 mJ / mm 3 , ≥10mJ / mm 3 , ≥15mJ / mm 3 , ≥20mJ / mm 3 , ≥25mJ / mm 3 , ≥30mJ / mm 3 , ≥35mJ / mm 3 , ≥40mJ / mm 3 , ≥45mJ / mm 3 , ≥50mJ / mm 3 or ≥55mJ / mm 3 In one embodiment, the condom has a tensile strength of ≥5 MPa, ≥8 MPa, ≥10 MPa, ≥12 MPa, ≥13 MPa, ≥14 MPa, or ≥15 MPa. In one embodiment, the condom has an elongation at break of ≥400%, ≥500%, ≥600%, ≥700%, ≥800%, ≥900%, or ≥1000%.
[0063] The condom of the first aspect of the present invention can be manufactured by a process comprising dipping a mold into a liquid formulation comprising copolymer X by conventional techniques. Alternatively, a film comprising copolymer X can be processed into a condom by thermoforming and / or vacuum forming. Condoms can also be manufactured by a process comprising extrusion or injection molding.
[0064] When the condom is formed by dipping the die, the edge of the material may then be curled (while still on the die) at the open end of the condom to form a "bead".
[0065] Preferably, after the basic condom shape has been formed and the film has been dried and / or cooled (depending on the forming process), it is swollen with an aqueous formulation or water. In one embodiment, the condom is hydrated in water or an aqueous formulation for at least 1 minute, at least 5 minutes, at least 10 minutes, at least 30 minutes, at least 1 hour, at least 4 hours, at least 8 hours, at least 12 hours, or at least 24 hours to reach its equilibrium water content. Preferably, hydration is carried out at room temperature, or at 20-60°C, 20-50°C, or 30-50°C. The required hydration time / temperature may vary depending on the thickness of the condom film.
[0066] The hydrated condom can then be sealed in a package. The condom can optionally be rolled up before or after the hydration step and before packaging.
[0067] A second aspect of the present invention provides a condom according to the first aspect enclosed in a packaging. This may be any suitable packaging known in the art, such as a foil package or a plastic container with a lid. Preferably, the condom is provided in a rolled-up state within the packaging. In one embodiment, the packaging does not contain a separate lubricant.
[0068] In a third aspect of the present invention, the condom is formed by dipping. Conventional dipping techniques can be used. For example, the mold can be immersed in a liquid containing copolymer X once or twice or more. The liquid can be, for example, an aqueous dispersion of copolymer X, a solution of copolymer X in an organic solvent (e.g., a polar solvent such as ethanol), or copolymer X dissolved or dispersed in an organic solvent / water mixture (e.g., an aqueous ethanol solution, preferably 1-20% v / v, 6-15% v / v, or 8-12% v / v of an aqueous ethanol solution). The liquid can contain copolymer X at a concentration of at least 1% by weight, at least 2% by weight, at least 3% by weight, at least 4% by weight, or at least 5% by weight; and / or at most 15% by weight, at most 14% by weight, at most 13% by weight, at most 12% by weight, at most 11% by weight, at most 10% by weight, or at most 9% by weight. For example, it can contain copolymer X at a concentration of 1-15% by weight, 3-12% by weight, or 5-9% by weight. The liquid can be prepared by dissolving or dispersing the copolymer X in water and / or an organic solvent at an elevated temperature, for example, at least 40° C., at least 50° C., at least 60° C., or at least 70° C., and / or at most 100° C., at most 90° C., or at most 80° C. As described above, the mold can be dipped sequentially into liquids containing different copolymers X, and / or into a liquid containing a blend of different copolymers X.
[0069] The copolymer can be dried at room temperature to form a film on the surface of the mold. Alternatively, it can be dried under heating and / or reduced pressure. When the mold is dipped more than once, a drying step can be performed after each dipping. Once the film is formed, it is hydrated in water or an aqueous formulation and the condom is removed from the mold. The condom can be rolled up (dried or hydrated), and a fluid material (such as a lubricant) can be optionally applied to the closed end of the condom in the rolled-up state. The condom may have undergone an electrical testing process before being rolled up.
[0070] Given the tendency of condom materials to swell and expand in water, it may be necessary to use a mold that is smaller than the desired size of the finished condom.
[0071] A fourth aspect of the present invention relates to the use of a film comprising copolymer X in hydrogel form as a physical barrier during sexual activity. The film can be in the form of a condom, as described in the first aspect of the invention. The film can also be a flat, thin film used as a barrier during sexual activity, such as between the mouth and genitals or anus during oral sex. Such a product is known in the art as a dental dam. The present invention can provide enhanced sensation and pleasure, and is therefore more attractive to consumers than existing commercial dental dams.
[0072] Example
[0073] The following non-limiting examples are intended to illustrate the present invention.
[0074] Example 1
[0075] A) Preparation of (UPy Precursor) Monomer A
[0076] In the presence of 5.2ml triethylamine, 2.38g (19mmol) of 2-acetylbutyrolactone and 3.3g (37mmol) of guanidine carbonate were refluxed in 20ml of absolute ethanol. The solution became yellow and turbid. After heating under reflux overnight, the solid was filtered, washed with ethanol, and suspended in water. The pH was adjusted to a value of 6-7 with HCl solution, and the mixture was stirred. Filtered, rinsed with water and ethanol, and then dried solid to obtain pure monomer A, i.e. 2-amino-4-hydroxy-5-(2-hydroxyethyl)-6-methyl-pyrimidine.
[0077] b) Synthesis of supramolecular polymers using hexanediol
[0078] 20 g (6.67 mmol) of telechelic hydroxyl-terminated PEG-3000 (M nThe mixture was dried under vacuum at 120°C for 2 hours (the weight ratio was 3000). Subsequently, 1.13 g (6.67 mmol) of monomer A from Example 1A, 6.99 g (26.7 mmol) of methylenedicyclohexane 4,4'-diisocyanate (HMDI) as monomer B, 50 ml of dimethylformamide, and 1 drop of dibutyltin dilaurate were added. The reaction mixture was stirred at 90°C. After 1 hour, 1.56 g (13.3 mmol) of 1,6-hexanediol as monomer D (molar ratio of hexanediol:PEG = 2:1; molar ratio of monomer B: total of monomers A+C+D = 1) was added. The reaction mixture was stirred at 90°C for 8 hours. The reaction mixture was then diluted with 50 ml of methanol and poured into 500 ml of diethyl ether. The precipitated polymer was dissolved in 70 ml of chloroform and 70 ml of methanol and poured into 500 ml of diethyl ether. The precipitated polymer was dried under vacuum to obtain a white solid with a weight-average molecular weight of 52 kDa.
[0079] c) Condom manufacturing
[0080] An 8-12% (v / v) aqueous ethanol solution was prepared and the polymer of Example 1B was dissolved in it at 70°C with stirring until a homogeneous solution with a concentration of approximately 5-9% by weight was obtained. The solution was cooled to 40°C to form a solution with the required viscosity for dipping. A glass mold was immersed in the polymer-containing liquid and shrunk, leaving a liquid layer on the surface. The mold was spin-dried at room temperature for 1 hour and then immersed a second time in the same liquid. The mold was spin-dried at room temperature for 16 hours, forming a second layer of hydrogel on the mold surface. The condom and mold were immersed in water at room temperature. After swelling for 5 minutes, the hydrogel condom separated naturally from the glass. The condom was allowed to equilibrate in water for an additional 24 hours. As it absorbed water, the condom swelled and increased in diameter. The finished hydrogel had a water content of approximately 73% and the condom was approximately 240 μm thick.
[0081] In its rolled state, the condom does not stick to itself and can be easily unrolled onto the penis without the need for any dusting.
[0082] d) Mechanical properties test
[0083] To illustrate its mechanical properties, a 2 cm wide ring was cut from the middle of the condom. The ring was measured using a tensile testing machine by stretching at 50 mm / min until the material broke. Elongation at break % and F max The maximum force measured during elongation is dependent on the condom thickness. Since the thickness is not precisely controlled in this model condom production method, this value is not reported in this paper. However, the following parameters are independent of condom thickness:
[0084] Stiffness: Tangent to the tensile curve from 0 to 2.5% elongation
[0085] E100: Young's modulus at 100% strain
[0086] Toughness: Area under the tensile curve
[0087] tensile strength
[0088] Example 2-13
[0089] The procedure of Example 1 was repeated using different PEGs and different molar ratios of hexylene glycol. The results are summarized in the table below.
[0090] It can be seen that increasing the molecular weight of the PEG monomer used increases water absorption when the molar ratio of hexanediol to PEG remains unchanged. This is presumably due to an increase in the hydrophilic component of the copolymer. Similarly, increasing the molar ratio of hexanediol to PEG, when the PEG molecular weight remains unchanged, reduces water absorption. However, at high PEG molecular weights, the effect becomes less pronounced. Thus, for PEG6000, the water absorption is already quite high and exhibits less variability as the hexanediol to PEG molar ratio changes compared to PEG1000, which has a lower average water absorption and is more strongly affected by the hexanediol to PEG molar ratio.
[0091] For a given PEG molecular weight, Young's modulus generally shows a small increase with increasing hexanediol to PEG molar ratio, with the exception of PEG 1000, which is very strongly affected by this ratio. For tensile strength, PEG 1000 appears to show a nonlinear trend with respect to the hexanediol to PEG molar ratio, while the results for PEG 3000 and PEG 4000 appear to be better than those for PEG 6000.
[0092]
[0093] Examples 14-22
[0094] The procedure of Example 1 was repeated similarly using different PEGs and different molar ratios of 1,12-dodecanediol instead of hexylene glycol. The results are summarized in the table below.
[0095] It can be seen that similar overall trends apply when using dodecanediol. Comparing Examples 15, 18, and 21, as well as 14 with 17, and 16 with 19, increasing the molecular weight of the PEG monomer used, while maintaining the same dodecanediol to PEG molar ratio, increases water absorption and results in condoms with greater flexibility and lower stiffness, but also lower toughness and strength. Increasing the dodecanediol to PEG molar ratio, while maintaining the same PEG molecular weight, reduces water absorption for at least PEG 6000 and PEG 4000. For PEG 6000, stiffness, toughness, and tensile strength all increase with increasing the diol to PEG molar ratio. However, for PEG 4000, toughness and tensile strength are better at a diol to PEG molar ratio of 4 than at ratios of 2 or 6. For PEG 3000, a diol to PEG molar ratio of 4.5 yields the best toughness, softness, and low stiffness of the tested ratios, while a molar ratio of 4 provides the highest tensile strength of the tested ratios.
[0096] Therefore, it is obviously important to select the best balance of all required mechanical properties. In the examples tested above, when using hexylene glycol, the best results generally seem to be obtained with PEG3000 and a molar ratio of hexylene glycol to PEG of 2-4, and with PEG4000 and a molar ratio of hexylene glycol to PEG of 5-6. Examples 11 and 12 (PEG4000, a molar ratio of hexylene glycol to PEG of 5 or 6) are the most preferred of these because high tensile strength and reasonably low E100 are balanced. When using dodecanediol, the best results generally seem to be achieved with PEG4000 and a molar ratio of diol to PEG of 4, and with PEG3000 and a molar ratio of diol to PEG of 4.5. For PEG3000, it is speculated that a molar ratio as high as 5 can also produce good results.
[0097] Among all the tested examples, Example 12 had the highest tensile strength, while Example 22 had the highest toughness with good tensile strength, sufficiently low stiffness and E100, and sufficiently high water absorption, followed closely by Example 21.
[0098]
[0099] The thickness of the condom can be adjusted by adjusting the solids content of the liquid with which the mould is dipped and / or by varying the number of dippings.
[0100] Porosity test
[0101] Condom samples were tested for leakage by filling with squid ink and visually observing any transfer of ink through the condom (at approximately 3000 Pa) following the procedure of Appl. Env. Microbiol., 1922, 3180. No ink transfer was observed for the condoms tested.
[0102] Transparency Test
[0103] Examples 12 and 13 were repeated to obtain condom samples having different thicknesses (60 μm for Example 12a and 400 μm for Example 13a). The condom samples were tested for clarity and color using UV / vis spectroscopy. Pieces of film, typically 1 cm x 1 cm in size, were cut from the condoms. These cut samples were placed on microscope slides made of 1 mm thick glass. The absorbance of these slides containing the different condom samples was measured at 350 nm and 400 nm using a double-beam UV / vis spectrophotometer, using a microscope slide without condom film as a reference. The measured absorbance was divided by the thickness of the condom film to calculate the absorbance per mm of thickness. The results were compared with those of two commercially available condoms made from natural rubber latex and synthetic polyisoprene, respectively.
[0104] The results show that while for NRL and PI condoms, it is important to make the condoms as thin as possible to achieve high transparency, for the condoms of the present invention, even relatively thick condoms can achieve very high transparency. The choice of using thicker condoms can also provide consumers with a different tactile effect.
[0105]
[0106] Thermal stability test
[0107] The rolled condom of the present invention was placed in a beaker and completely submerged in water at 20°C for 24 hours. The resulting fully swollen condom, submerged in water, was placed in a 70°C oven for 24 hours, ensuring that the condom remained completely submerged throughout the entire period. The beaker was then removed from the oven and allowed to cool to room temperature for 4 hours. The rolled condom was then removed from the water and placed on a glass mold, where it was gently unrolled and observed.
[0108] Condoms made with hexylene glycol performed well at room temperature, but when subjected to stability testing, some stickiness and brittleness appeared in the condoms (although these were very extreme stability conditions and the condoms were still functional). Condoms made with dodecanediol showed increased heat resistance in this regard. This is believed to be related to the fact that dodecanediol is more nonpolar and has a higher melting point (80°C compared to 40°C). There is a stronger microphase separation with the hydrophilic PEG block, and the H-bonding of the UPy units becomes stronger due to the more nonpolar local environment.
Claims
1. A condom comprising a copolymer X obtainable by polymerization of monomers A, B, C and D; Wherein monomer A is one or more (preferably one) compounds of the following formula: Where R 1 and R 2 independently selected from H and C1-C1 optionally substituted with hydroxyl, primary or secondary amine groups 20 Alkyl, provided that R 1 and R 2 One of them has a hydroxyl, primary or secondary amine group; Monomer B is one or more (preferably one) of the formula OCN-R 3 -NCO diisocyanate compound, wherein R 3 =C4-C 20 an alkylene group, which may optionally be cyclic or branched; Monomer C is one or more (preferably one) hydroxyl-terminated telechelic polyalkylene glycol compounds having a number average molecular weight of 1000 to 10,000 and preferably linear; Monomer D is one or more of the formula HO-R 4 -OH diol compound, where R 4 C2-C 20 Alkylene, which may be interrupted by 1 to 5 heteroatoms selected from the group consisting of O, N and S, preferably 1 O atom, and / or preferably wherein R 4 For straight chain; in, The molar ratio of monomers D to C is 0.1:1 to 10:
1.
2. The condom of claim 1, wherein the molar ratio of monomer D to C is at least 0.5:1, at least 1:1, at least 2:1, at least 3:1, at least 4:1, or at least 5:1; and / or no more than 9:1, no more than 8:1, no more than 7:1, or no more than 6:
1.
3. A condom as claimed in claim 1 or 2, wherein monomer C is one or more compounds each having the following number average molecular weight: at least 1500Da, at least 2000Da, at least 2500Da, at least 3000Da, at least 3500Da, or at least 4000Da; and / or no more than 9000Da, no more than 8000Da, no more than 7000Da, no more than 6000Da, no more than 5000Da, or no more than 4500Da; preferably, wherein monomer C is one or more compounds each having a number average molecular weight of 3000 to 5000Da, and the molar ratio of monomer D to C is 3:1 to 6:
1.
4. A condom as claimed in any one of the preceding claims, wherein R 1 and R 2 One of the following is selected from H and unsubstituted C1-C 20 Alkyl, and R 1 and R 2 The other is a C1-C 20 Alkyl; preferably, wherein R 1 is H or C1-C3 alkyl, preferably methyl, and / or wherein R 2 It is a C1-C5 alkyl group substituted by a hydroxy group, preferably -CH2CH2OH.
5. A condom as claimed in any one of the preceding claims, wherein R 3 For C9-C 15 Alkylene, preferably C 13 Alkylene, preferably, wherein monomer B is methylene-dicyclohexyl-4,4'-diisocyanate, or the compound of monomer B comprises methylene-dicyclohexyl-4,4'-diisocyanate.
6. A condom as claimed in any one of the preceding claims, wherein in at least one compound of monomer D, R 4 C4-C 18 Alkylene, preferably C5-C 14 Alkylene, preferably C6-C 12 Alkylene, preferably not interrupted by any heteroatoms, optionally wherein monomer D is 1,6-hexanediol, 1,4-cyclohexanedimethanol or 1,12-dodecanediol.
7. A condom as claimed in any one of the preceding claims, wherein the copolymer X is obtainable by the following process: monomers A, B and C are reacted together in the same reaction mixture to form a reaction product, which is then polymerized with monomer D; or monomers A, B, C and D are reacted together in the same reaction mixture to form a reaction product.
8. The condom according to any one of the preceding claims, wherein the copolymer X is a random copolymer.
9. A condom as claimed in any one of the preceding claims, wherein: The copolymer X has a weight average molecular weight of 5 to 140 kDa, preferably ≥10 kDa, ≥20 kDa, ≥30 kDa, ≥40 kDa, ≥50 kDa, ≥60 kDa or ≥70 kDa; and / or ≤130 kDa, ≤120 kDa, ≤110 kDa, ≤100 kDa, ≤95 kDa, ≤90 kDa, ≤85 kDa or ≤80 kDa; preferably 50-110 kDa.
10. A condom as claimed in any one of the preceding claims, which has been hydrated with water so that the copolymer X is in the form of a hydrogel; preferably, wherein the condom contains water in an amount of ≥20 wt. %, ≥30 wt. %, ≥40 wt. %, ≥50 wt. %, ≥60 wt. %, ≥65 wt. % or ≥70 wt. %; and / or ≤95 wt. %, ≤90 wt. %, ≤85 wt. %, ≤80 wt. % or ≤75 wt. %; preferably 55 to 85 wt. %.
11. The condom of claim 10 which has been hydrated with water, said water containing a dissolved or dispersed lubricant, preferably wherein said lubricant is carrageenan.
12. A package enclosing a condom as claimed in any one of the preceding claims.
13. The package of claim 12, wherein no separate lubricant is present in the package.
14. A method of manufacturing a condom, comprising: Providing a liquid comprising a copolymer X as defined in any one of claims 1 to 9; immersing the mold in the liquid; drying to form a film of copolymer X on the mold; and The film is hydrated to form a hydrogel.
15. Use of a film in the form of a hydrogel comprising a copolymer X as defined in any one of claims 1 to 11 as a physical barrier during sexual activity.
Citation Information
Patent Citations
Strong reversible hydrogels
EP1972661A1
Condom system and method for making
US20150313752A1
Elastomeric condom
US5195537A
Hydrogen bonded hydrogels
WO2006118460A1
Supramolecular biodegradable polymer
WO2014185779A1